Investigation of informational technologies in freight forwarding - Batarlienė, Nijolė (Transport, 2003)
This article examines types of informational technologies application problems, shows their scheme, observes basic data structures of technological problems, principles and methods of modeling these structures. It is noted that the solution of transport technology problems is based on the improvement of technological supply, the rational usage of informational modeling methodology of the whole transportation process. There are informational search and presentation computerized technologies when indexation and coding system are used to create them. As an example, dangerous freight forwarding resolution codification is shown, which is used for searching the most important resolutions and for their presentation to all the dangerous freight-forwarding participants. The present informational search and presentation programs that improve the possibilities of the presented search are observed as well. First Published Online: 19 Dec 2011